2016
DOI: 10.1073/pnas.1601626113
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of natural transformation by an RNA chaperone and a multitarget small RNA

Abstract: A highly conserved DNA uptake system allows many bacteria to actively import and integrate exogenous DNA. This process, called natural transformation, represents a major mechanism of horizontal gene transfer (HGT) involved in the acquisition of virulence and antibiotic resistance determinants. Despite evidence of HGT and the high level of conservation of the genes coding the DNA uptake system, most bacterial species appear non-transformable under laboratory conditions. In naturally transformable species, the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(205 citation statements)
references
References 44 publications
8
177
0
Order By: Relevance
“…Our discovery of a large class of ProQ-associated sRNAs opens the door for further studies of this potential domain of posttranscriptional control, which will likely reveal molecular mechanisms and physiological roles of RNA in bacteria. Indeed, a recent study in Legionella identified a ProQ-like protein as a matchmaker of sRNA-mRNA interactions in the regulation of bacterial competence (46).…”
Section: Resultsmentioning
confidence: 99%
“…Our discovery of a large class of ProQ-associated sRNAs opens the door for further studies of this potential domain of posttranscriptional control, which will likely reveal molecular mechanisms and physiological roles of RNA in bacteria. Indeed, a recent study in Legionella identified a ProQ-like protein as a matchmaker of sRNA-mRNA interactions in the regulation of bacterial competence (46).…”
Section: Resultsmentioning
confidence: 99%
“…This region, delineated by residues R32, R69, R80, R100, K101, K107, and R114 (Fig. 2B, left panel) surrounds a surface patch identified on the homologous L. pneumophila RocC protein that is important for RNA binding and protein function (Attaiech et al 2016). This positively charged surface patch also maps to a conserved protected region in our HDX experiments, indicating this area is important for RNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…However, ProQ has now emerged to function more broadly as a global sRNA binding protein in Salmonella, and a similar role is predicted for proteins containing ProQ/FinO domains found in divergent bacterial species (Smirnov et al 2016). In Legionella pneumophila, a ProQ/FinO domain protein has been shown to be required for regulation of an sRNA controlling natural competence (Attaiech et al 2016).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hypothetical proteins such as HP1334 in H. pylori and several other RNA binding proteins such as YbeY in Sinorhizobium meliloti have been implicated with chaperone activity5758. More recently, a ProQ/FinO domain containing protein Lpp0148 has been reported to function as a RNA chaperone in Legionella pneumophila 59. It is, therefore, possible that R. conorii proteins with unknown function may play a role in sRNA-mediated regulation.…”
Section: Discussionmentioning
confidence: 99%